Comparative Study of In-Furnace and Out-Furnace Coal Blending on Performance Acceptance in Ultra Supercritical Coal-Fired Power Plants - Kurniawan, Tito; Hantoro, Ridho (Journal of Earth Energy Science, Engineering, and Technology, 2025)
This study aims to improve fuel flexibility in ultra-supercritical coal-fired power plants through an optimal coal blending strategy. This is important because this type of power plant faces challenges in coal availability, operational reliability, and energy efficiency, and must comply with increasingly stringent emission regulations. However, determining the ideal coal blend remains a challenge due to the difficulty of balancing aspects of performance, emission levels, production costs, and overall operational impacts. In this study, the Multi Criteria Decision Making (MCDM) method with a goal programming approach is used to optimize the proportion of coal blending in the boiler (in-furnace) and out-furnace. This study is important to ensure that ultra-supercritical coal-fired power plants can meet energy demand more flexibly, efficiently, and sustainably in the face of changing coal supply conditions and environmental policies. The study tested various coal calorific values ​​(from 5200 to 4200 kCal/kg) optimally used individually (single coal) and mixed. Coal blending optimization was carried out on 4 parameters using five types of coal to fill five boiler silos, obtaining an improvement in sulfur parameters of 6.3%, coal price parameters of 0.85%, HHV parameters of 0.54% and slagging-fouling index parameters of 5.64%.